ANALISIS NORMATIF TIDAK DIKEMBALIKANNYA UANG SISA LELANG BARANG GADAI MENURUT HUKUM PERDATA - ALHABSYI, YASER ARAFAT (Ganec Swara, 2025)
Pawning is an agreement made between a creditor and a debtor in which the debtor hands over a movable object to the creditor to guarantee the repayment of a pawn debt, when the debtor fails to carry out his performance. Meanwhile, what is meant by Auction is the sale of goods which is open to the public with written and/or verbal price offers which increase or decrease to reach the highest price, which is preceded by an Auction Announcement. This study employs the normative legal research method, which is defined as "research methods on legislation both from the perspective of the hierarchy of legislation (vertical) and the harmonious relationship of legislation (horizontal)".The remaining money from the auction is the remaining money from the sale of pawned goods that have been auctioned by the company because the customer is no longer able to pay the obligation after deducting administration fees. The remaining money from this auction is the customer's right and must be returned to the customer. If the creditor does not return the remaining money from the auction of the pawned goods, the debtor has the right to sue the creditor for losses.